The farmer empowerment to reduce the chemical risk poisoning through liquid organic fertilizers usage - Charloq; Mahyuni, Eka Lestari (Talenta Publisher, 2020)
The high frequency of chemicals use such as fertilizers and pesticides in intercropping planting patterns giving farmers a high risk of poisoning exposure. This devotion applies the appropriate technology in organic ponds to produce Liquid Organic Fertilizer (POC). The use of POC is horticultural farmers empowered which is useful for improving poor organic soil conditions and producing organic products with the object of chili and vegetable crops. POC applied to soil and plants can increase agricultural growth and production, thus providing a strong basis for farmers to reduce chemical use. The results of the treatment were observed through plant growth and production, accompanied by intensive assistance, as innovations applied in this PPM activity. The resulting output is the effectiveness of POC which is applied to chili and vegetable crops. Empowerment activities show a significant development in which soil conditions become more fertile, leaf thickness increases and becomes greener, plant stems are stronger, pest and disease attacks can be suppressed. This community dedication is very beneficial for the farming community and helps in creating healthy farmers and the environment.